Contested landscapes: territorial conflicts and the production of different ruralities in Brazil - Fernandes, Bernardo Mançano [UNESP]; Welch, Cliff (Taylor & Francis, 2019)
From the perspective of Brazilian agrarian geography, the conflicts generated by land tenure disputes have as protagonists the families of the Landless Workers’ Movement (Movimento dos Trabalhadores Rurais Sem Terra), traditional landowners, and agribusiness corporations. In this article, we present a reflection on land conflicts and the spatial and territorial production of latifundia, peasant smallholders, and large-scale agribusiness through studies of the landscapes of two municipalities in the state of São Paulo. Among the various tools for analysing territorial disputes, Google Earth can be used for local, regional, and international comparative studies of how landscapes have been transformed. Informed by traditional research, the article analyses a diversity of photographs, from satellite to field shots, as evidence of landscapes that express conflicting social relations in disputes over different models of social and territorial development.
Keywords: agrarian capitalism; Agrarian reform; Brazilian peasantry; landless workers movement (MST)